Bioinformatics analysis of the wheel treadmill test on motor function recovery after spinal cord injury. Issue 4 (9th December 2021) - Wang, Qiu‐Lin; Li, Ting‐Ting; Fang, Chang‐Le; Zhang, Bao‐Lei
Abstract: This study aimed to explore the possible target and mechanism of the wheel treadmill (WTM) test for motor function recovery of spinal cord injury (SCI). Rats were divided into sham, control and WTM groups to establish an SCI mode. Rats in the WTM group were trained on the WTM test, and Basso–Beattie–Bresnahan (BBB) scores were determined. The samples were collected, and mRNA sequencing was conducted to determine the changes in gene expression. The coexpressed genes were screened to construct a protein–protein interaction (PPI), followed by the Kyoto Encyclopedia of Genes and Genomes pathway and Gene Ontology function enrichment analysis, and the differentially expressed genes (DEGs) volcano map and hub gene expression heat map were constructed using R language. The BBB scores in the control and WTM groups increased with time, with the WTM group scoring higher than the control group. The results of rat spinal cord tissue sequencing showed that a total of 1679 DEGs were screened in the sham and control groups; 928 DEGs and 731 overlapping genes were screened in the WTM and control groups. The key genes were identified by PPI analysis. One hundred and thirty‐three genes were found to be overlapping by combined analysis of spinal cord sequencing data and BBB scores of rats at Week 7. The top 10 DEGs from high to low were T yrobp, Rac2, Cd68, C1qb, Aif1, Cd74, Spi1, Fcer1g, RT1‐D A, and Ccl4 . The terms with the highest enrichment scores were microglia‐mediated positive regulation of cytotoxicity and major histocompatibility complex class II protein complexes. Treatment with the WTM test promotes recovery of motor function after SCI in rats by modulating intercellular communication and immune function. Abstract : The Basso–Beattie–Bresnahan scores in the control and wheel treadmill (WTM) groups increased with time, with the WTM group scoring higher than the control group. The WTM test promoted motor function recovery of spinal cord injury (SCI) rats by regulating the expression of Tyrobp, Rac2, Cd68, Aif1, and other genes. Treatment with the WTM test promotes recovery of motor function after SCI in rats by modulating intercellular communication and immune function.